العلاقات التركية الأفريقية بعد 2002: حكومة تركية جديدة وواقع ثنائي مختلف - بقاص, خالد (جامعة الوادي University of Eloued, 2017)
تهدف الدراسة إلى بحث التوجه التركي الجديد نحو القارة الأفريقية خصوصا بعد وصول حزب العدالة والتنمية إلى الحكم في تركيا نهاية سنة 2002، والذي أعلن عن مجموعة من الفعاليات والمشاريع الهادفة لتطوير واقع العلاقات التركية الأفريقية وخاصة مع الدول الواقعة جنوب الصحراء، غير أن ما يميز نظرة حكومة حزب العدالة - باعتبارها المبادر الرئيس لتطوير العلاقات - هي توجهها الشامل لجل مجالات التعاون السياسية والدبلوماسية والاقتصادية والتجارية والأمنية إضافة إلى المساعدات الإنسانية والتنموية التي كانت بمثابة داعم قوي لتطوير العلاقات الثنائية ولزيادة ثقة الأفارقة بجدية الأتراك في الارتقاء بالعلاقات الثنائية. Abstract: The study aims to discuss Turkey's new orientation towards the African continent, especially after the arrival of the Justice and Development party(AKP) to power in Turkey by the end of the year 2002, which announced a series of events and projects aimed at the development of the reality of the Turkish-African relations, especially with countries situated in the south of the Sahara (Sub Saharan States), but what distinguishes the vision of the government of Justice party -as the main initiator to develop relations- is a mass-oriented for most of the fields : political, diplomatic, economic, trade and security cooperation, in addition to humanitarian and development assistance which was a strong supporter of the development of bilateral relations and to increase the confidence of Africans that the Turks are serious about improving bilateral relations.
Keywords: السياسة الخارجية؛ العلاقات التركية؛ الدبلوماسية؛ القارة الافريقية